Anticoagulant Utilization Evaluation in a Tertiary Care Teaching Hospital: An Observational Prospective Study in Medical in Patients - Singh, Vijay; Gopinath, Krishnappa; Behzadpour, Amirali; Kasturiranagan Meera, Neelathahalli (Indian Journal of Pharmacy Practice)
Introduction: Drug utilization evaluation of anticoagulant drugs is essential considering the spectrum of use and associated risks with their therapy. Objectives: The objectives of the present study were to evaluate the drug utilization pattern of anticoagulants, identify and assess drug interactions and ADRs with the use of anticoagulants. Method: 84 patients from the medicine department were included in this prospective, cross sectional study conducted for one year. Results: Heparin was mainly used for prophylaxis. Enoxaparin and acenocoumarol were other commonly used drugs. The diagnosis varied from Ischemic heart disease (IHD), deepvein thrombosis (DVT), pulmonary embolism (PE), cardiovascular accident and others. Laboratory tests like prothrombin time (PT), international normalized ratio (INR), activated partial thromboplastin time (aPTT), in few cases radiological tests were performed to monitor the therapy. Use of mono therapy and combination therapy aswell as topical use of heparingel was observed. Acenocoumarol and warfarin were the drugs prescribed at discharge. 35 drug interactions were identified, twelve pharmacokinetic and twenty three pharmaco dynamic in nature. Acenocoumarol was the most commonly identified drug with drug interactions. Pharmacokinetic mechanism commonly found was inhibition of vitamin Kactivity; synergistic effect was the mechanism of pharmaco dynamic interaction. Sixteen interactions were severe in intensity.6 adverse drug reactions (ADRs) were observed during the study. Conclusion: The pharmacotherapy with anticoagulant drugs should be cost effective and with minimum risks involved. The study highlights the importance of following the guidelines for appropriate use of anticoagulants.
Keywords: Anticoagulant; Drug utilization pattern Prothrombin time; Drug interactions; International normalized ratio